An organizational perspective on artscience collaboration: Opportunities and challenges of platforms to collaborate with artists - Claudia Schnugg; BeiBei Song (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Artists are often seen as innovators and producers of creative and extraordinary new ideas. Additionally, experiencing art and artistic processes is an important opportunity for learning and exploration. Thus, corporations and scientific organizations have experimented with initiatives that generate artscience collaboration, such as fellowships, long-term collaborations with artists, and artist-in-residence programs. Looking at outcomes in the long-term, it is possible to identify important contributions to scientific, technological, and artistic fields that stem from artscience collaboration opportunities in organizations. On the other hand, it is often difficult to define immediate tangible outcomes of such processes as innovation as interdisciplinary interaction and learning processes are valuable experiences that do not always manifest directly in outcomes that can be measured. Drawing from cases of artscience programs and qualitative interviews with program managers, scientists, and artists, this article explores how artscience collaboration in an organization adds value and helps overcome organizational challenges regardless of such outcomes. By shifting the focus from the outcome to the process of artscience collaboration, it is possible to discover in more depth value-added contributions of artscience experiences on an individual level (e.g., new ways of knowing and thinking, understanding of materials and processes, and learning). Moreover, such contributions tell stories of connecting the process of artscience programs to the organizations' goals of developing a new generation of leaders and driving a more adaptive, innovative culture. These benefits of artscience opportunities need to be supported by managerial activities in the organization. Thus, it enables a more differentiated understanding of possible contributions of artscience collaboration to organizations and helps to define the best model to create such opportunities. The article also recommends future research directions to further advance artscience collaboaration, especially in light of pertinent movements such as STEAM and Open Innovation, and promising developments in related fields such as neuro-aesthetics.
Keywords: 650; art and innovation; art and technology; artist residency program; artist-in-residence; arts-based initiatives; artscience; artscience collaboration; interdisciplinary collaboration